Clinical Experience with PEGylated Hyaluronic Acid Fillers: A 3-year Retrospective Study - Rauso, Raffaele; Nicoletti, Giovanni Francesco; Bove, Pierfrancesco; Rauso, Giuseppe M.; Fragola, Romolo; Lo Giudice, Giorgio; Zerbinati, Nicola (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Hyaluronic acid fillers are the most used worldwide, thanks to the high biocompatibility and safety profile of HA and it is also the only substance that can be “dissolved” due to the hyaluronidase effect. AIM: A retrospective clinical evaluation of the outcomes following PEG cross-linked HA-based filler injection was performed. METHODS: Data were collected from December 2017 to June 2020. A total of 65 patients (12 M, 53 F), age ranging 28–62 year’s old (mean age 42.3), were treated. Exclusion criteria were applied and in accord to treatment plan, were used specific site injections and fillers. Follow-up was evaluated between 6 months and 2 years. RESULTS: A total of 61 treatments using 124 vials of HA filler crosslinked with PEG were performed. CONCLUSION: In conclusion, from 2014, HA fillers having PEG as cross-linker agent have been introduced in the european market. Several papers have been published in order to evaluate the features of these fillers, although, to the best of our knowledge, this is the first clinical paper regarding their use.